Neurodevelopmental outcome in very low birthweight infants with pathological umbilical artery flow. Issue 3 (24th August 2015) - Brütsch, Simonne; Burkhardt, Tilo; Kurmanavicius, Juozas; Bassler, Dirk; Zimmermann, Roland; Natalucci, Giancarlo; Ochsenbein-Kölble, Nicole
Abstract : Objective: To assess neurodevelopmental outcome during toddlerhood in very low birthweight (VLBW) infants with absent or reverse end-diastolic flow (AREDF) in the umbilical artery (UA) during pregnancy. Design: Retrospective cohort study with matched control group. Setting: Tertiary perinatal centre. Patients and outcome measures: We compared longitudinally collected data on neonatal and neurodevelopmental outcomes among 41 infants born in our institution from 1997 to 2010 with birth weight <1500 g and UA AREDF and 41 infants with prenatally normal UA Doppler parameters matched for gestational age, birth weight, sex and year of birth. We evaluated neurodevelopmental outcome at a median (range) corrected age of 23.3 (10.1–29.6) months using the Bayley scales of infant development, 2nd edition (BSID-II), and neurological examination. Results: The mental development index in UA AREDF children (median (range) 84 (49–116)) was significantly lower than in controls (median (range) 91 (62–140)), including after adjustment for confounders. Intergroup differences in psychomotor development index (PDI; BSID-II) and the rate of cerebral palsy or minor neuromotor dysfunction were non-significant. Conclusions: VLBW infants with UA AREDF have a higher risk of poorer mental development during toddlerhood than controls matched for gestational age, birth weight, sex and year of birth. UA AREDF may be considered a prenatal predictor of poorer mental development in this population. Long-term follow-up studies with larger cohorts are needed to better evaluate the impact of this prenatal factor on later neurodevelopment.